2008
DOI: 10.1007/s00423-008-0338-y
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of mediastinal goiter: risk factors for sternotomy

Abstract: Surgical management of patients with mediastinal goiter is the therapeutic modality that requires considerable experience of the surgical team, performed in specialized centers, and appropriate preoperative diagnostic management. Statistically significant risk factors for sternotomy are as follows: recurrent goiter, primary mediastinal goiter, posterior mediastinal location of goiter, and the presence of an aberrant adenoma situated in the mediastinum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 17 publications
1
53
1
Order By: Relevance
“…Furthermore, attempts to establish any significant correlation between the patients' clinical features and the actual surgical procedure always proved fruitless. [10][11][12][13][14] In the present study, we found that extension of the goiter below the level of the aortic arch appeared to be a significant predictive factor for the need for sternotomy, displaying an OR of almost 33. Conversely, the lack of radiologic extension beyond the aortic arch predicted successful transcervical removal of mediastinal goiters without sternotomy.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Furthermore, attempts to establish any significant correlation between the patients' clinical features and the actual surgical procedure always proved fruitless. [10][11][12][13][14] In the present study, we found that extension of the goiter below the level of the aortic arch appeared to be a significant predictive factor for the need for sternotomy, displaying an OR of almost 33. Conversely, the lack of radiologic extension beyond the aortic arch predicted successful transcervical removal of mediastinal goiters without sternotomy.…”
Section: Discussionsupporting
confidence: 49%
“…In this study, we defined mediastinal goiters as only goiters extending below the thoracic inlet by at least 3 cm at CT scan evaluation with the neck in hyperextension, as this is 1 of the most widely accepted definitions. 10,17,18 Nevertheless, studies including only goiters reaching or descending below the aortic arch, 12 or having >50% of the mass located below the thoracic inlet, 19 or even with any extent of the gland below the thoracic inlet have also been published. 20,21 If we had used less selective inclusion criteria and comprised goiters with any part of the gland extending below the thoracic inlet (378 thyroids in the same study period), then the duration of mediastinal goiter's history would have not resulted as a risk factor for sternotomy (OR 2.78; 95% CI 0.95-8.16; p ¼ .07), whereas its extension below the level of the aortic arch would have been an even stronger predictor of sternal incision at operation (OR ¼ 34; 95% CI, 11-104; p < .0001).…”
Section: Discussionmentioning
confidence: 99%
“…Sternotomy is performed in about 0-11% of cases. This wide range may be explained by the lack of a common SG definition (2,5,6,(11)(12)(13). In this study, sternotomy or thoracotomy were not applied, all patients were operated through cervical approach.…”
Section: Discussionmentioning
confidence: 99%
“…Sternotomy is performed in about 0 to 11% cases. This wide range may be explained by the absence of a common SG definition (6,7,(10)(11)(12)(13). Most of the SG studies have been published as series of author's self-experience, evaluation of their own surgical techniques and comparison of other studies on SG.…”
Section: Introductionmentioning
confidence: 99%
“…Success rates of greater than 99% have been reported using the cervical approach, [12] while other studies have shown that up to 30% of patients require thoracic intervention. [13] Again, the incidence of extra-cervical approach being required is affected greatly by which definition of retrosternal goitre is used. Most studies state an incidence of around 10% or lower.…”
Section: Introductionmentioning
confidence: 99%